2020
DOI: 10.1097/ta.0000000000002584
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of measurement properties of health-related quality of life instruments for burns: A systematic review

Abstract: BACKGROUND: Health-related quality of life (HRQL) is a key outcome in the evaluation of burn treatment. Health-related quality of life instruments with robust measurement properties are required to provide high-quality evidence to improve patient care. The aim of this review was to critically appraise the measurement properties of HRQL instruments used in burns. METHODS: A systematic search was conducted in Embase, MEDLINE, CINAHL, Cochrane, Web of Science, and Google scholar to reveal articles on the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…In this process, the feasibility of instruments should also be considered as well; instruments should be easy and quick to use and should be low-cost or free of charges. Similar systematic reviews investigating the measurement properties according to the COSMIN checklist are available for diseases similar to CMN such as vitiligo, vascular malformations, capillary malformation and burn scars 17 , 23 , 24 , 25 . Although these studies also revealed a low quality of measurement instruments validated for their particular patient population, some of their recommendations may inform which instruments should be validated for CMN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, the feasibility of instruments should also be considered as well; instruments should be easy and quick to use and should be low-cost or free of charges. Similar systematic reviews investigating the measurement properties according to the COSMIN checklist are available for diseases similar to CMN such as vitiligo, vascular malformations, capillary malformation and burn scars 17 , 23 , 24 , 25 . Although these studies also revealed a low quality of measurement instruments validated for their particular patient population, some of their recommendations may inform which instruments should be validated for CMN.…”
Section: Discussionmentioning
confidence: 99%
“…Disease-specific instruments measure the impact of a specific condition on the different aspects of ‘quality of life’, while generic instruments measure the overall ‘quality of life’ of a subject, allowing comparisons between a group of patients with a certain disease and their peers of the general populations. The systematic review evaluating ‘quality of life’ instruments for burn scars showed that burn scar specific instruments have the best measurement properties 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Important advantages of the EQ-5D are its short form, so it can be applied worldwide as shown by a recent burn study in Tanzania [8], its availability in many languages, and the ability to assess the burden of disease by calculating DALYs [9] and cost-effectiveness of burn care by calculating QALYs [10]. However, because it does not include burn-specific problems, such as itching, disfigurement, fatigue, or cognition, a (potential) limitation of the EQ-5D is its seemingly limited sensitivity for burn-specific problems [11,12].…”
mentioning
confidence: 99%
“…Within burns, the EQ-5D is sometimes applied with an extra cognition item as it is assumed to increase the sensitivity and comprehensiveness of the EQ-5D for burns [7,20,21]. However, this has not yet been formally studied [11]. Previous studies showed that cognition problems are negatively associated with burn severity [20,22].…”
mentioning
confidence: 99%